Are we fully exploiting type I Interferons in today's fight against COVID-19 pandemic?. (August 2020) - Aricò, Eleonora; Bracci, Laura; Castiello, Luciano; Gessani, Sandra; Belardelli, Filippo
Graphical abstract: Highlights: IFN-I, in particular IFN-β, are promising drugs for SARS-CoV2 infection. Early infection in elderly patients is the best setting to exploit IFN-I immunomodulatory activity. Caution should be given in using continuous IFN-I treatments at high doses. Mucosal IFN-I delivery is promising but deserves further clinical investigation. Attention should be paid to IFN-I treatment in patients with severe COVID-19. Abstract: Coronavirus disease 2019 (COVID-19) first emerged in late 2019 in China. At the time of writing, its causative agent SARS-CoV-2 has spread worldwide infecting over 9 million individuals and causing more than 460, 000 deaths. In the absence of vaccines, we are facing the dramatic challenge of controlling COVID-19 pandemic. Among currently available drugs, type I Interferons (IFN-I) – mainly IFN-α and β –represent ideal candidates given their direct and immune-mediated antiviral effects and the long record of clinical use. However, the best modalities of using these cytokines in SARS-CoV-2 infected patients is a matter of debate. Here, we discuss how we can exploit the current knowledge on IFN-I system to tailor the most promising dosing, timing and route of administration of IFN-I to the disease stage, with the final aim of making these cytokines a valuable therapeutic strategy in today's fight against COVID-19 pandemic.